Investigation of tribological behaviour of a-C:H coatings for dry deep drawing of aluminium alloys - Zhao, Rong; Steiner, Jennifer; Andreas, Kolja; Merklein, Marion; Tremmel, Stephan (Tribology International, 2017)
Lubricant‑free sheet metal forming increases resource efficiency and contributes to environmental protection. One approach to reducing friction and wear in dry forming is the tool-sided application of carbon-based coatings. In this work, amorphous hydrogenated carbon (a‑C:H) coatings were prepared by plasma‑enhanced chemical vapour deposition (PECVD). The coating samples were deposited under different amounts and ratios of acetylene (C2H2) and argon (Ar) gas atmospheres. The coating samples were characterized regarding their thickness, roughness and mechanical as well as chemical bond structures. The tribological behaviour against aluminium alloys was investigated under lubricant‑free conditions with a ring‑on‑disc tribometer. The relationships between chemical bond composition and coating properties were clarified. Finally, one a-C:H coating variant with promising tribological performance against aluminium alloys was exemplarily tested in a flat strip drawing test, which models the tribological conditions in the flange area of a deep drawing process.
Keywords: Dry sheet metal forming; DLC; aluminium; adhesive wear